Pengembangan Modul Ajar PAI Berbasis Karakter Religius pada Materi Bukti Beriman di SMAN Kabuh Jombang - Raya Agung Wirayudha Zaen; Machnunah Ani Zulfah; Muhammad Fodhil (Lembaga Yasin AlSys, 2025)
Religious character education plays a crucial role in shaping students’ morality amidst increasingly complex moral and social challenges. Instructional modules that integrate religious character values serve as essential instruments for realizing holistic and meaningful Islamic Religious Education (PAI) learning. At SMAN Kabuh Jombang, there is a clear need for the development of innovative teaching materials capable of effectively instilling religious character, particularly in the topic of evidence of faith. This study aims to develop a religious character-based PAI instructional module that is valid, practical, and effective, and to evaluate its feasibility. The research employed the Research and Development (R&D) method using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects included PAI teachers and students at SMAN Kabuh Jombang. Data were collected through expert validation questionnaires (content and media), user response questionnaires, and student learning outcome tests, then analyzed using both quantitative and qualitative descriptive methods. The findings indicate that the developed module achieved a very high validity rating from experts, received positive responses from teachers and students, and demonstrated effectiveness in enhancing both content understanding and the internalization of religious character. The study concludes that the religious character-based PAI instructional module meets the criteria of being valid, practical, and effective, and serves as an innovative alternative for embedding religious values in students. The implications of this research include contributions to PAI curriculum development, practical guidance for teachers in integrating character values, and opportunities for developing similar modules in other areas of PAI content.